Foundations of climate change denial: Anti-environmentalism and anti-science - Peter J. Jacques; Riley E. Dunlap (PLoS ONE, 2025)
Despite a longstanding scientific consensus about the reality of anthropogenic global warming (AGW), a climate change countermovement (CCCM) has worked to undermine and cast doubt on climate science for over three decades. The CCCM is a coalition led by fossil fuel corporations and their advocacy organizations, far-right conservative think tanks (CTTs), conservative foundations and a few dissenting scientists that has successfully thwarted domestic mitigation policies and international agreements aimed at reducing greenhouse gas emissions (GHGs). Social science investigations into the CCCM have become increasingly sophisticated and have provided key insights into the content and influence of AGW denial narratives. Denial narratives reject the basic findings of climate science: the earth is warming (trend denial), largely due to human actions (attribution denial), producing harmful impacts (impact denial), and mitigation policies are ineffective or harmful (policy denial). These narratives cast the integrity of climate science and scientists in doubt; yet a fine-grained analysis of denial narratives has not been conducted. To fill this gap, we analyze the content of 108 books that reject climate science using a two-stage content analysis approach: first, a deductive approach to identify denial claims in the books, and second an inductive approach to analyze the larger semantic ecosystems surrounding the claims. We confirm the major narratives that have been identified in prior research, but discover a consistent, underlying anti-environmentalism along with a rejection of “impact science” that highlights the negative effects of industrial production. These two meta-themes challenge reflexive modernization, which relies on scientific knowledge and global environmentalism to solve environmental problems. This reflects a deep “anti-reflexivity” employed to combat forces promoting the need for major reductions in GHGs and a shift to renewable energy. This anti-reflexive DNA of climate denial serves to protect power and privilege systems formed since industrialization, which has been powered by fossil fuels.